The Methodologies of Open Social Scholarship - J. Matthew Huculak (KULA, 2019)
Implicit in the notion of understanding and enacting open social scholarship is that there is something broken with the current model of scholarly communication. This introduction outlines issues in the current models of academic publication while the essays explore potential futures in the academic publishing industry.